ACTIVE ROLES OF NGOs AND CBOs TO PROMOTE ENTREPRENEURS’ PASSION AND DRIVE IN THE TOWNSHIPS AND RURAL AREAS OF SOUTH AFRICA - Mofolo, Malefetsane (Advances in Social Sciences Research Journal, 2020)
In South Africa, entrepreneurial spirit is regarded as fundamental to the future development of the country. To that effect, regulatory reforms have been introduced, and others are still to be introduced to stimulate and bring about change to the entrepreneurial activity. Again, for instance, in some provinces non-governmental organisations (NGOs) and community based organisations (CBOs) have been established. A point in case is that in North West Province, Chambers of commerce have been established to mobilise and facilitate relations between government and business community on issues related to the economy and enterprise development programmes. However, when one analyses these, one develops a sense that genuine aspects related to less tangible components of entrepreneurial activity, such as the drive for passion, enthusiasm, motivation and attitudes, have been partially stimulated through government programmes in South Africa, especially in townships and rural communities. Therefore, in order to position the contestation of this article, a desktop approach was adopted, where existing theoretical and empirical documents were consulted to highlight the discourse around these issues and the recent policy developments targeted to accelerate growth and development of small, medium and micro-enterprises (SMMEs), including co-operatives. The findings from the literature show the disposition of government to support entrepreneurship endeavours, and challenges related to, inter alia, awarding of government contacts and access to markets. Consequently, the active roles of NGOs and CBOs as government partners to ensure entrepreneurs’ passion and drive in the townships and rural areas of South Africa are recommended.